Legal Consequences of Parking Management in the City of Surabaya in Realizing Good and Clean Governance - Parikesit, Mumpuni Dimas; Gunawan, Bambang Panji; Romadhon, Ahmad Heru (Dinasti Research, 2025)
The phenomenon of illegal parking has evolved into a serious problem in urban areas, including the city of Surabaya. Although the Surabaya City Government has established various regulations to organize the parking system, violations of these provisions still frequently occur, causing disturbances to traffic order, the comfort of road users, and the aesthetic value of the city. This article aims to analyze the legal implications of parking practices that are not in accordance with applicable laws and their impact on efforts to organize effective, efficient, and sustainable urban transportation governance. This study includes an analysis of the parking management system implemented, the authority and responsibility of law enforcement officials, as well as the obstacles to its implementation. This article also offers alternative solutions based on technological innovations and data-driven approaches to strengthen an orderly and equitable parking system. The results of this study are expected to serve as normative and applicative recommendations for the Surabaya City Government.